Tracking of physical activity in adolescents between 2010 and 2014 - Paula Roldão da Silva; Géssika Castilho dos Santos; Waynne Ferreira de Faria; Renan Camargo Corrêa; Rui Gonçalves Marques Elias; Antonio Stabelini Neto (Universidade Federal de Santa Catarina, 2018)
Even though the benefits of regular physical activity (PA) are well established, national tracking studies are still scarce. The aim of the study was to analyze the tracking of physical activity (PA) in 2010, 2012 and 2014 of adolescents from Jacarezinho, Paraná. Adolescents (ages: 15.6 ± 0.6 years) were evaluated in 2014, who had participated in the 2010 and 2012 surveys. The Baecke questionnaire was used to evaluate the physical activity fields: school, sports and leisure time. ANOVA for repeated measures was used to compare the physical activity index (PAI) in years 2010, 2012 and 2014. The Spearman correlation coefficient was used to relate PAI obtained in 2014 with previous years. Significant reduction was observed in both sexes in the total and school index in 2012 and 2014 in relation to 2010. The leisure time index also presented a significant reduction in male sex from 2012 to 2014 (p<0.05). In the correlation between 2014 and the previous years, boys demonstrated weak association in the leisure index in 2010 (rho=0.292). In the female sex, values were significant in the leisure time and total indexes (rho=0.263; rho=0.307) in 2010 and in the sports and total indexes (rho=0.337; rho=0.332) in 2012. The research indicates that PA of adolescents decreased with age advancement, resulting in low to moderate tracking.